Information relevance perspective: Boosting market engagement through social influencer-generated content - Dharomesz, Vonezyo Yupanzara; Adyantari, Api (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
The businesses are developing dynamically and need brilliant ideas to be sustainable in the market. One of them is using influencers as an effective tool for their marketing activities. Although some studies discuss how influencers are one of the most effective marketing tools, few discuss the relationship between the influencers and social media users. Therefore, businesses must know several factors that may influence this relationship between the two. This study is based on the theory of information relevance. Therefore, the findings have been presented to show the link between influencer-generated content with emotional attachment and the quality of the information in deducing the relationship between influencers and consumers on social media. Results from 230 respondents indicated that influencer-generated content that is interesting, updated, reliable, and understandable to consumers is more able to increase the emotional interest of consumers in the influencers. Reliability and understandability contribute positively to information quality. This encourages the consumer to follow or recommend the influencer to many on social media. This can also boost the popularity of influencers on social media. The study should help researchers and businesses improve their understanding of the social media relationship between influencers and consumers. In addition, it also offers recommendations regarding influencer performance management for businesses.